THE SWISS MODEL OF RELATIONS WITH THE EU AFTER THE YEAR 2021 - Daniil Yu. Menchikov (Научно-аналитический вестник Института Европы РАН, 2023)
In the article, the peculiarities of the Swiss model of relations with the EU are considered. The political and economic aspects are distinguished. The first category includes, among other is- sues, the alignment with the EU foreign policy, preserving, nevertheless, the own principles of neu- trality and sovereignty, as well as an active participation in the EU programs. The next important feature of the Swiss model of relations with the EU is integration to a significant extent of the EU law into the Swiss legislation. The economic features include an active participation of Switzerland in the European Single Market, and politisation of issues of economic cooperation by the European Union. A possible impact of suspending the negotiations on the institutional framework agreement in 2021 at the Swiss initiative is studied. The author concludes that the mentioned impact has been so far quite small, as the relations are progressively developing. It can be explained by the theory of economic interdependence of R. Keohane. The scientific significance of the work lies in a small ex- tent of investigation of the topic of the Swiss model of relations with the EU, as well as the study of the impact of long-term factors on the EU relations with third states. The chosen methods are con- tent analysis and synthesis.